Regional Anesthesia Subarachnoid Blockade (RASAB) in Scoliosis Patients - Setijanto, Eko; Putra, Kiel Pino (Faculty of Medicine-Universitas Airlangga, 2023)
Introduction: Scoliosis is a three-dimensional spinal deformity that is mainly determined based on the lateral curvature of the spine. Furthermore, regional anesthesia often infiltrates the peripheral nerves with an anesthetic agent and blocks transmission to avoid or relieve pain. A previous study revealed that scoliosis in patients is one of the factors affecting the success of spinal anesthesia. Objective: To obtain a theoretical basis that can support the solution to the RASAB problem. The acceptance of the theory is the first step to providing a better understanding of the study problem based on the scientific framework of thinking. Furthermore, the similarities, differences, and views of several pieces of literature that discussed related issues were evaluated in this review. Review: Regional anesthesia subarachnoid blockade (RASAB) or spinal anesthesia, is a procedure, which involves the administration of local anesthetic drugs into the subarachnoid space. Furthermore, the process is carried out between the lumbar (L) vertebrae L2-L3, L3-L4, or L4-L5. Spinal anesthesia is often used in surgical procedures involving the lower abdomen, pelvis, perineum, and lower extremities. Conclusion: In the setting of scoliosis, spinal anesthesia is challenging, but is not an absolute contraindication. Patients with scoliosis have unique characteristics, hence, anesthetists need to understand the impact of the disease on the body.